HIPPO -- an adaptive open hyptertext system - Newton, Paul K. (1998)
The hypertext paradigm offers a powerful way of modelling complex knowledge structures. Information can be arranged into networks, and connected using hypertext links. This has led to the development of more open hypertext design, which allow hypertext services to be integrated seamlessly into the user's environment. Recent research has also seen the emergence of adaptive hypertext, which uses feedback from the user to modify objects in the hypertext. The research presented in this thesis describes the HIPPO hypertext model which combines many of the ideas in open hypertext research, with existing work on adaptive hypertext systems. The idea of fuzzy anchors are introduced which allow authors to express the uncertainty and vagueness which is inherent in a hypertext anchor. Fuzzy anchors use partial truth values which allow authors to define a "degree of membership" for anchors. Anchors no longer have fixed, discrete boundaries, but have more in common with contour lines used in map design. These fuzzy anchors are used as the basis for an adaptive model, so that anchors can be modified in response to user actions. The HIPPO linking model introduces linkbase trees which combine link collections into inheritance hierarchies. These are used to construct reusable inheritance trees, which allow authors to reuse and build on existing link collections. An adaptive model is also presented to modify these linkbase hierarchies. Finally, the HIPPO system is re-implemented using a widely distributed architecture. This distributed model implements a hypertext system as a collection of lightweight, distributed services. The benefits of this distributed hypertext model are discussed, and an adaptive model is then suggested.